Cholesterol Synthesis Increased in the MMI-Induced Subclinical Hypothyroidism Mice Model - Yongfeng Song; Xiujuan Zhang; Wenbin Chen; Ling Gao (International Journal of Endocrinology, 2017)
Subclinical hypothyroidism (SCH) is defined as increased serum thyroid-stimulating hormone (TSH) concentrations and normal serum thyroid hormone (TH) levels as well as an increased serum cholesterol level, which is an important cause of secondary hypercholesterolemia and cardiovascular diseases. Some studies have demonstrated a direct effect of TSH on cholesterol metabolism via in vivo and in vitro experiments. However, because no suitable SCH model has been established until now, the changes in cholesterol synthesis that occur in SCH patients remain unknown. Here, we establish an SCH mouse model by using long-term low-dose MMI administered in drinking water. Compared with the control group, the MMI-treated mice had elevated circulating TSH levels, but the serum FT3 levels in these mice did not change. Additionally, the TC levels increased in both the serum and liver of the experimental mice. Both the protein expression and activity of hepatic HMGCR, the rate-limiting enzyme for cholesterol synthesis in the liver, increased in these mice. We also found that the SCH mice had decreased phospho-HMGCR and phospho-AMPK expression, while the expression of AMPK showed no change. In conclusion, we established a suitable SCH model in which cholesterol synthesis is increased.